Associated Bacteria and Their Effects on Growth and Toxigenicity of the Dinoflagellate Prorocentrum lima Species Complex From Epibenthic Substrates Along Mexican Coasts - Tarazona-Janampa, Ulrike I.; Cembella, Allan D.; Pelayo-Zárate, María C.; Pajares, Silvia; Márquez-Valdelamar, Laura M.; Okolodkov, Yuri B.; Tebben, Jan; Krock, Bernd; Durán-Riveroll, Lorena M. (Frontiers in Marine Science, 2020)
The dinoflagellate genus Prorocentrum is globally represented by a wide variety of species found upon benthic and/or epiphytic substrates. Many epibenthic Prorocentrum species produce lipophilic polyether toxins, some of which act as potent protein phosphatase inhibitors and tumor-promoters associated with Diarrheic Shellfish Poisoning (DSP). Most members of the P. lima species complex (PLSC) commonly found in the tropics and sub-tropics are toxigenic. Epiphytic and planktonic bacteria co-occur with toxigenic Prorocentrum but reciprocal allelochemical interactions are under-investigated. The aim of the present study was to identify the culturable bacteria collected together with isolates of the PLSC from seagrass (Thalassia testudinum) and macroalgae (Laurencia sp. and Sargassum sp.) along tropical Mexican coasts, and to explore potential species interactions with selected isolates. Twenty-one bacterial genera belonging to Proteobacteria, Actinobacteria and Bacteroidetes were identified by amplification of the 16S rRNA gene marker from nine clonal Prorocentrum cultures, with γ-proteobacteria comprising the dominant class. A positive correlation was found between the bacterial genera associated with two Prorocentrum clones and the esterified toxin analog DTX1a-D8, but there was no apparent correlation between the other PLSC clones and their associated bacteria with the other five DSP toxins detected. No bacteriostatic or allelochemical response was found for cell- and culture medium extracts of five Prorocentrum isolates assayed for bioactivity against Staphylococcus sp. DMBS2 and Vibrio sp. HEL66. Bulk cell-washing of Prorocentrum PA1, followed by growth with antibiotics, was only effective in reducing bacterial load in the initial growth stages, but did not yield axenic cultures or lower bacterial cell densities throughout the culture cycle. Antibiotic treatment did not impair growth or survival of the dinoflagellate, or apparently affect DSP toxin production. There was no significant correlation between Prorocentrum cell volume, growth rate, bacterial cell counts or cellular toxin concentration over the entire time-series culture cycle. Benthic Prorocentrum and associated bacterial communities comprise highly diverse and characteristic microbiomes upon substrates, and among compartments in culture, but this study provides little evidence that allelochemical interactions among Prorocentrum cells and associated bacteria originating from epibenthic substrates play a definable role in growth and toxigenicity.